2004
DOI: 10.1024/0036-7281.146.12.561
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: taux de portage chez les ovins de la région de Marrakech (Mnabha)

Abstract: Toxoplasma gondii is an ubiquitous parasite with a prevalence variable from country to country. In Morocco very few studies were devoted to this prevalence. To fill this gap we were interested to study the epidemiology of this parasite and to know the level of carriage by the different vectors which are the sources of contamination in humans. The study was done by directly detecting the cysts in the cerebral tissue of the 50 sheep killed and destined for consumption. The results of this preliminary study show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Indeed, the few studies carried out since the 1970s to evaluate the seroprevalence of toxoplasmosis in humans have shown that it varied from one city to another, ranging from 33.3% among women of child bearing age in Marrakech city to 50.6% among pregnant women in Rabat city 12,13 , however the national prevalence of toxoplasmosis remained unknown. Moreover, in order to know the rate of T. gondii carriage by animals intended for human consumption and consequently their role in the contamination by this parasite, an epidemiological study, have been carried out in 2004 by Belbacha and collaborators 14 , in Marrakech on sheep and revealed a rate of 30%, which is very close to that found by Sawadogo and collaborators in 2005 15 . Otherwise, a lower prevalence of 9.87% was found in cattle in 2008 16 , in the same region.…”
Section: Introductionsupporting
confidence: 59%
“…Indeed, the few studies carried out since the 1970s to evaluate the seroprevalence of toxoplasmosis in humans have shown that it varied from one city to another, ranging from 33.3% among women of child bearing age in Marrakech city to 50.6% among pregnant women in Rabat city 12,13 , however the national prevalence of toxoplasmosis remained unknown. Moreover, in order to know the rate of T. gondii carriage by animals intended for human consumption and consequently their role in the contamination by this parasite, an epidemiological study, have been carried out in 2004 by Belbacha and collaborators 14 , in Marrakech on sheep and revealed a rate of 30%, which is very close to that found by Sawadogo and collaborators in 2005 15 . Otherwise, a lower prevalence of 9.87% was found in cattle in 2008 16 , in the same region.…”
Section: Introductionsupporting
confidence: 59%
“…Results of the study revealed that cysts of Toxoplasma were found in 15 out of the 50 sheep tested, 30.0%. In order to confirm the reports of the previously mentioned study, the cerebral specimens were inoculated into mice, which was the first time and may be the last time in which mouse bioassay technique was used in Morocco for the detection of Toxoplasma [47]. Moreover, and this time in the city of Marrakesh, a similar study was also conducted whereby blood samples of 261 sheep were collected and examined through the ELISA technique.…”
Section: B Toxoplasma Gondii In Animalsmentioning
confidence: 88%
“…Organs and tissues, derived from the approximately 350 species of receptive vertebrates, which are infected with tachyzoites and bradyzoites are sources of infec-tion for the final hosts-cats. They can also be sources of infection for intermediate hosts (Belbacha et al 2004;Figliuolo et al 2004;Silva et al 2007). Other sources of infection are wild rodents, small birds and wild rabbits, which are believed to be the natural source of infection for cats (Hill et al 1998;Dubey 2002;Figueroa-Castillo et al 2006).…”
Section: Sources Of Infection In Toxoplasmosismentioning
confidence: 99%